PECULIARITIES OF THE FIBROSIS AND CIRRHOSIS MONITORING AMONG CHILDREN WITH CHRONIC LIVER DISEASES - A.N. Surkov; I.E. Smirnov; A.S. Potapov; A.G. Kucherenko; E.L. Tumanova (Педиатрическая фармакология, 2009)
The researchers examined the opportunities to use determination in the serum among children with chronic liver diseases of various etiologies of the hyaluronic acid levels, collagen type IV, matrix metalloproteinase-2, tissue inhibitor of the matrix proteinases 1 in diagnostics of the liver fibrosis degree. They have found out that children with the given pathology show significantly growing concentrations of these compounds against marked fibrotic changes in the liver parenchyma. Hyaluronic acid, collagen type IV and matrix metalloproteinase 2 may be reliable noninvasive cirrhosis markers and used to monitor the efficiency of therapy for the chronic liver diseases among children.Key words: matrix metalloproteinase-2, tissular inhibitor of the matrix proteinases 1, liver cirrhosis, markers, diagnostics, children.